Risk of Dementia and Death in the Long Term Follow Up of the Pittsburgh CHS Cognition Study - Kuller, Lewis H. (Alzheimers Dement, 2015)
INTRODUCTION: Increasing life expectancy has resulted in a larger population of older individuals at risk of dementia. METHODS: The Cardiovascular Health Study–Cognition Study (CHS-CS) followed 532 participants from 1998–99 (mean age 79) to 2013 (mean age 93) for death and dementia. RESULTS: Risk of death was determined by extent of coronary artery calcium, high-sensitivity cardiac troponin, and brain natriuretic peptide, and white matter grade. Significant predictors of dementia were age, apolipoprotein-E4, vocabulary raw score, hippocampal volume, ventricular size, cognitive performance, and number of blocks walked. By 2013, 160 of 532 were alive, including 19 cognitively normal. Those with normal cognition had higher grade education, better cognition test scores, greater hippocampal volume, faster gait speed, and number of blocks walked as compared to survivors who were demented. DISCUSSION: Few survived free of dementia and disability. Prevention and delay of cognitive decline for this older population is an imperative.